2016
DOI: 10.1002/ecm.1234
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycling and export in California chaparral: the role of climate in shaping ecosystem responses to fire

Abstract: Climate change models predict that interannual rainfall variability will increase in California over the next several decades; these changes will likely influence how frequently California ecosystems burn and how they respond to fire. Fires uncouple N mobilization from uptake by destroying plant biomass and increasing nitrification. Following fire, autumn and winter rains can leach N into streams from slopes that have been denuded. The amount of N exported depends on how rapidly soil microbes metabolize it int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 68 publications
(136 reference statements)
2
35
0
Order By: Relevance
“…We then use these values to investigate the influence of different combinations of N_decay and Ksat0 pairs on the concentration-discharge patterns. (Shields & Tague, 2012) and plot scale nitrogen cycling (Hanan et al, 2016b). The range of values of key parameters (N_decay, Ksat0) overlaps with the settings in the previous modeling studies (Hanan et al, 2016b) or derived from previous studies (Demenico & Schwartz, 1990 *From Physical and Chemical Hydrogeology (Demenico & Schwartz, 1990), the hydraulic conductivity ranges from 8 ×10 −13 m/s (unweathered marine clay) to 3 ×10 −2 m/s (gravel).…”
Section: Initial Calibrationsupporting
confidence: 57%
See 1 more Smart Citation
“…We then use these values to investigate the influence of different combinations of N_decay and Ksat0 pairs on the concentration-discharge patterns. (Shields & Tague, 2012) and plot scale nitrogen cycling (Hanan et al, 2016b). The range of values of key parameters (N_decay, Ksat0) overlaps with the settings in the previous modeling studies (Hanan et al, 2016b) or derived from previous studies (Demenico & Schwartz, 1990 *From Physical and Chemical Hydrogeology (Demenico & Schwartz, 1990), the hydraulic conductivity ranges from 8 ×10 −13 m/s (unweathered marine clay) to 3 ×10 −2 m/s (gravel).…”
Section: Initial Calibrationsupporting
confidence: 57%
“…Rattlesnake Creek watershed (5.8 km 2 area) is located on the southern facing slopes of the coastal Santa Ynez Mountains and has three dominant shrub species: Ceanothus megacarpus (big pod ceanothus), Adenostoma fasciculatum (chamise) and Arctostaphylos spp. (Manzanita) (Hanan et al, 2016b). The watershed is characterized by steep slopes (slopes >20 ) and sandy loams plus rock outcrops.…”
Section: Study Sitesmentioning
confidence: 99%
“…RHESSys couples elements of the ecosystem models BIOME‐BGC (Running & Hunt, ) and CENTURY (Parton, Schimel, Cole, & Ojima, ), with distributed watershed models to derive the coupling between ecosystem water use, carbon and nitrogen cycling with lateral soil water redistribution. RHESSys has been widely used to estimate spatially distributed soil moisture, ET, surface and subsurface run‐off, carbon and nitrogen cycling in different biomes and under different climate and land use change scenarios (e.g., Band, Patterson, Nemani, & Running, ; Bart, Tague, & Moritz, ; Garcia, Tague, & Choate, ; Hanan, Tague, & Schimel, ; Hwang et al, ; Lin, ; Lin, Webster, Hwang, & Band, ; Miles & Band, ; Tague & Band, ). RHESSys uses a landscape hierarchical structure over nested patch (Figure ), hillslope and watershed scales (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the role of drought and fire on soil biogeochemical processes, it has been shown that soil nutrient availability, microbial activity, and biomass decrease under post‐fire severe drought conditions (Potts, Suding, Winston, Rocha, & Goulden, ; Hinojosa et al, ; Hinojosa, Parra, Laudicina, & Moreno, ; Hanan, Tague, & Schimel, ). However, under moderate drought (15% rainfall reduction), Hedo de Santiago, Lucas‐Borja, Wic‐Baena, Andrés‐Abellán, and Heras () showed that soil enzyme activities, microbial biomass, and respiration were not affected during a period of 3 years in a medium‐age (17 years since the last fire) forest.…”
Section: Introductionmentioning
confidence: 99%